2006
DOI: 10.1080/09513590600624317
|View full text |Cite
|
Sign up to set email alerts
|

Contraception in perimenopausal women with diabetes mellitus

Abstract: Comparing lipid levels and hemostatic variables as a function of glycosylated hemoglobin level, we conclude that diabetes control has greater influence on these parameters than the type and dose of steroids involved in the contraceptive devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 10 publications
0
33
0
Order By: Relevance
“…Most, but not all (26;27), studies evaluating cyproterone- (28;29) , desogestrel- (30), drospirenone-(31) , norethindrone- (32), or levonorgestrel-(33) containing OC did not report increases in LDL, even in women with disorders associated with insulin resistance, such as polycystic ovary syndrome, history of gestational diabetes, or diabetes. One study reported an increase in mid-cycle LDL by 2.2% and 5.7% with ethinylestradiol 35mcg and norgestimate over 12 and 24 month (7).…”
Section: Discussionmentioning
confidence: 99%
“…Most, but not all (26;27), studies evaluating cyproterone- (28;29) , desogestrel- (30), drospirenone-(31) , norethindrone- (32), or levonorgestrel-(33) containing OC did not report increases in LDL, even in women with disorders associated with insulin resistance, such as polycystic ovary syndrome, history of gestational diabetes, or diabetes. One study reported an increase in mid-cycle LDL by 2.2% and 5.7% with ethinylestradiol 35mcg and norgestimate over 12 and 24 month (7).…”
Section: Discussionmentioning
confidence: 99%
“…Three articles met the criteria for the evaluation of laboratory parameters in diabetic women while using an IUD [3032]. The disposition of potential papers is given as a flow chart (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have also shown that COC and DMPA use among diabetic women affected lipid levels but did not impact risk for myocardial infarction [40][41][42]. Studies generally have not shown effects on other sequelae such as retinopathy or renal function in diabetic women using hormonal methods [43,44].…”
Section: Diabetesmentioning
confidence: 95%
“…Some studies have shown worsening of short-term markers of diabetes control, such as insulin requirements or blood glucose levels, in diabetic women using COCs [40,41]. Studies have also shown that COC and DMPA use among diabetic women affected lipid levels but did not impact risk for myocardial infarction [40][41][42].…”
Section: Diabetesmentioning
confidence: 96%